TEORI PEMBELAJARAN SOSIAL KRUMBOLTZ'S - Fadilla Sri Lestari; Fatma Mutia; Intan Kurnia Wati; Syifa Mardhiyyah; Salsabilla Salsabilla; Mhd Subhan (STAI Ihyaul Ulum Gresik, 2025)
Guidance and counseling play a crucial role in developing students' potential and career planning through various learning experiences. The theory developed by John D. Krumboltz emphasizes that career choice and development are not the result of chance, but are shaped through a lifelong learning process. Four key factors influencing career decisions include genetic inheritance, environmental conditions, learning experiences, and task-based skills. This study used a literature review method by searching relevant national and international journals, textbooks, and proceedings from the past five years. The analysis indicates that counselors can utilize this theory to help clients change maladaptive behaviors, improve decision-making skills, and prevent career problems. Learning through observation, imitation, and experience is key to planning an adaptive career path. These findings confirm the relevance of Krumboltz's Theory in developing career guidance programs in schools and universities.